ACCEPTANCE TOWARDS TOURISM DEVELOPMENT: THE CASE OF PERHENTIAN ISLAND - Mohamad, Diana; Mohamed, Badaruddin (PLANNING MALAYSIA, 2018)
Island tourism in Malaysia is gaining the globe’s attention and has attracted people from all over the world to come to Malaysia. Islands of Malaysia have been continuously developed for the purpose of providing the visitors’ with better and exclusive tourism experience. Perhentian Island is one of Malaysia’s premier tourism spots famous for its crystal clear water, uncrowded beaches in addition to turtle and baby shark snorkelling points. It is learned that intense development and steady growth of tourist arrivals to this island have somehow created various positive and negative impacts. It is realized that tourism development is pressured by the need to cater to the visitors’ demands while pays limited attention to the locals’ needs and acceptance level. This paper reports on the tourism development impacts on Perhentian Island, looking from the point of view of locals engaged in tourism sector. Employing quantitative research approach, selfadministered questionnaire was developed with the aim of assessing the locals’ acceptance level pertaining changes in social structure of Perhentian Island and negative influences of tourism development on the environment. The findings showed immediate intervention is required for re-establishment of the social structure, followed by environmental management.